Urinary NGAL incorporation into Renal Angina Index for early detection of acute kidney injury in critically ill children - Zeid, Ali Mohammed Abu; Mohammed, Doaa Youssef; AbdAlazeem, Amal Saeed; Seddeeq, Anas Saad Elsayed mohammed; Elnaany, Ashraf Mohamed (Journal of Clinical Nephrology, 2019)
Background and objectives: New AKI biomarkers (on the top of it NGAL biomarker) have demonstrated better performance for prediction of AKI in critically ill patients with heterogeneous illness. Renal angina index was recently reported to enhance prediction of severe AKI at the time of intensive care unit admission. This study tested the hypothesis that incorporation of uNGAL in patients with renal angina improves the prediction of severe AKI. Design, setting, participants & measurements: In our study 53critically ill children admitted to the pediatric intensive care unit in Zagazig university hospital, Measurement of urine neutrophil gelatinase– associated lipocalin (uNGAL) was determined individually by ELISA kit and in combination with the RAI which is calculated in each critically ill child for severe AKI. Statistical analysis was done for these data. Results: Individual uNGAL demonstrated marginal discrimination for severe AKI (area under curve [AUC]: NGAL, 0.877), little higher than prediction by RAI (AUC=0.847). Incorporation of uNGAL significantly added to the renal angina index AKI prediction (AUC=0.847, increased to 0.893). Conclusion: This study shows that incorporation of uNGAL into the RAI improves detection ability of severe AKI in critically ill children.